2022
DOI: 10.3390/ijms232113096
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Nicotinamide Riboside Administration Has a Cardioprotective Effect in Chronic Doxorubicin-Induced Cardiomyopathy

Abstract: Doxorubicin, which is widely used to treat a broad spectrum of malignancies, has pronounced dose-dependent side effects leading to chronic heart failure development. Nicotinamide riboside (NR) is one of the promising candidates for leveling the cardiotoxic effect. In the present work, we performed a comparative study of the cardioprotective and therapeutic actions of various intravenous NR administration modes in chronic doxorubicin-induced cardiomyopathy in Wistar rats. The study used 60 mature male SPF Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Nevertheless, it is important to mention that compared to previous reports [24,68,74,83,84] using biosynthetic precursors, such as NMN, NR and Nicotinic acid riboside (NAR) in animal models of Doxo-induced toxicity, we demonstrated that NMN supplementation is sufficient to improve the physical capacity impaired by Doxo using a clinically relevant route of administration and a concentration (500 mg/kg/day) that is below the recently reported NOAEL (No-Observable Adverse Effect Level) for NMN in Sprague Dawley rats [37].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, it is important to mention that compared to previous reports [24,68,74,83,84] using biosynthetic precursors, such as NMN, NR and Nicotinic acid riboside (NAR) in animal models of Doxo-induced toxicity, we demonstrated that NMN supplementation is sufficient to improve the physical capacity impaired by Doxo using a clinically relevant route of administration and a concentration (500 mg/kg/day) that is below the recently reported NOAEL (No-Observable Adverse Effect Level) for NMN in Sprague Dawley rats [37].…”
Section: Discussionmentioning
confidence: 82%
“…However, to the best of our knowledge, the results presented here are the first to demonstrate that the oral NMN administration preserves the exercise capacity in a context of chemotherapeutic regimen. Interestingly, a recent study has shown that the intravenous administration of another biosynthetic NAD+ precursor, NR (300 mg/kg) in Wistar rats subjected to a chronic Doxo treatment (10 mg/kg cumulative dose) has little to no effect on exercise capacity at 30-and 60 days post Doxo administration [83]. Therefore, additional studies are needed to compare different NAD+ biosynthetic precursors in the same experimental conditions and animal models in order to identify the most efficient NAD+-boosting strategy to counteract Doxo-induced side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…and TNF-α, via modulation of HIF/VEGF and cGMP/cAMP/SIRT signaling pathways [54]. Nicotinamide riboside administration was shown to exert a cardioprotective property against chronic DOXinduced cardiomyopathy [55]. These findings provide new ways of DOX-induced cardiomyopathy prevention and treatment approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Tissue fibrosis was reported in mice exposed to DOX [21,30], and epithelial-to-mesenchymal transition (EMT) along with endothelial-to-mesenchymal transition (EndoMT) are crucial in excessive myofibroblast generation and progression of fibrosis. The mesenchymal marker alpha-smooth muscle actin (α-SMA) was activated in resident fibroblasts during cardiac fibrosis [31].…”
Section: Nmn Supplementation Alleviates Fibrosis Of Heart Liver and L...mentioning
confidence: 99%
“…As a fundamental molecule in cells, NAD + plays key roles in energy metabolism and mitochondrial function and is involved in counteracting DNA damage and oxidative stress [20]. Supplementing the NAD + precursor nicotinamide riboside (NR) may efficiently alleviate DOX-induced cardiomyopathy by promoting DNA repair and mitochondrial homeostasis [21]. Nicotinic acid riboside (NAR) treatment attenuates DOX-induced myocardial injury through the Nrf-2/p62 pathway [22].…”
Section: Introductionmentioning
confidence: 99%